Comparison of different momentum control variables on assimilating radar observations for the forecasts of a dispersive convective event - Song, Wei; Lin, Erliang; Qiu, Xiaobin; Xue, Yuting (Frontiers in Earth Science, 2023)
In this study, the effects of BE using the stream function ψ and unbalanced velocity potential χu as momentum control variables (CV5 scheme) and BE using the velocity U and V as momentum control variables (CV7 scheme) on assimilating radar radial velocity and reflectivity data for short-term forecasts of dispersive convection in a weak environmental field were explored based on the weather research and forecasting model (WRF) model and its 3DVAR assimilation system. The 4 km resolution forecast samples are generated to formulate the CV5 and CV7 background error covariance (B) by the National Meteorology Center (NMC) method. The single-observation experiments reveal that the differences between the two BE statistics are mainly reflected on the momentum control variables. The increment of wind field from CV7 shows more small-scale local characteristics. Comparing with control experiment, real radar observation assimilation tests of CV5 and CV7 both improve the reflectivity and precipitation forecasts. But the CV7 scheme improve the forecasting of strong convective systems in weak environmental fields better than CV5. First, the results show that using the CV7 scheme to assimilate radar data improves both reflectivity dispersive precipitation forecasts more and significantly reduce the spurious precipitation forecasted by the CV5 scheme. In addition, CV7 also significantly reduces the forecast errors of surface variables and the wind analysis from CV7 is more local. Further analysis shows that the CV7 improves the water vapor convergence conditions compared to the CV5 scheme, which may be the reason for its better performance in the subsequent forecasts.